Prescription of Preexposure Prophylaxis to Men Who Have Sex With Men Diagnosed and Reported With Gonorrhea, STD Surveillance Network, 2016. Issue 8 (August 2018) - Ramirez, Viani; Han, Emily; Stoltey, Julie; Nguyen, Trang Q.; Pathela, Preeti; Tourdot, Laura; Walters, Jaime; Bell, Teal; Torrone, Elizabeth; Stenger, Mark
Abstract : Abstract: Using a representative sample of gonorrhea cases in select jurisdictions, we estimated the proportion of eligible men who have sex with men reporting being prescribed preexposure prophylaxis (PrEP) to prevent HIV infection. In 2016, half (51.3%) of the estimated 33, 165 eligible men who have sex with men reported being prescribed PrEP by their health care provider. Abstract : In 2016, 49% of all reported gonorrhea cases occurred among men who have sex with men. Of these men who have sex with men, 33, 165 were eligible for preexposure prophylaxis; half were prescribed preexposure prophylaxis by their health care provider.